2020
DOI: 10.4196/kjpp.2020.24.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of fully automated classification of whole slide images based on deep learning

Abstract: Although microscopic analysis of tissue slides has been the basis for disease diagnosis for decades, intra- and inter-observer variabilities remain issues to be resolved. The recent introduction of digital scanners has allowed for using deep learning in the analysis of tissue images because many whole slide images (WSIs) are accessible to researchers. In the present study, we investigated the possibility of a deep learning-based, fully automated, computer-aided diagnosis system with WSIs from a stomach adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
(41 reference statements)
0
25
0
Order By: Relevance
“…16 In our previous study for a normal/tumor classifier in stomach cancer, we tried to solve the class imbalance problem with a modified loss function. 17 However, we concluded that it is not easy to obtain a balanced performance with hugely imbalanced training data for DL-based tissue classifiers. Thus, we decided to limit the number of MSS patients to 1.5 times that of the MSI-H patients and randomly selected 126 MSS patients for our study (Table S1).…”
Section: Patient Cohortmentioning
confidence: 88%
“…16 In our previous study for a normal/tumor classifier in stomach cancer, we tried to solve the class imbalance problem with a modified loss function. 17 However, we concluded that it is not easy to obtain a balanced performance with hugely imbalanced training data for DL-based tissue classifiers. Thus, we decided to limit the number of MSS patients to 1.5 times that of the MSI-H patients and randomly selected 126 MSS patients for our study (Table S1).…”
Section: Patient Cohortmentioning
confidence: 88%
“…Deep learning did not perform optimally when there was a huge imbalance between classes[ 19 ]. In a previous study, we failed to obtain the balanced performance in tissue classification tasks unless the dataset itself was forced to have similar numbers between the classes[ 20 ]. Thus, we limited the difference in patient numbers between the mutation group and wild-type group by less than 1.4 fold through a random sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the tissue/non-tissue classifier, the Inception-v3 model was used without any parameter changes to train the normal/tumor classifiers for the 360 × 360-pixel patches at 20× magnification. We adopted the inception-v3 model because it was superior for the normal/tumor discrimination task than other CNN architectures in our previous study [13]. Deep neural networks were implemented using the TensorFlow deep learning library (http://tensorflow.org).…”
Section: Normal/tumor Classifiers For the Tcga Tissue Datasetsmentioning
confidence: 99%
“…In contrast to other classic machine learning approaches, deep learning can learn relevant features for given tasks directly from raw input datasets, and thus eliminate the necessity of domain-specific feature extraction processes [10]. Combined with huge digital WSI datasets, deep learning has been rapidly adopted for the pathologic diagnosis tasks such as Gleason grading of prostate cancer [4], detection of invasive ductal carcinoma in breast cancer [11], detection of metastasis for breast cancer [12], and detection of tumor tissues in gastric cancer [13].…”
Section: Introductionmentioning
confidence: 99%